THE IMPLEMENTATION OF MGLAB NETLUX SOFTWARE IN LISTENING FOR PROFESSIONAL CONTEXT CLASS - Teguh Bangkit Pamungkas; Novita Sumarlin Putri (Universitas Sarjanawiyata Tamansiswa, 2020)
This study is aimed to investigate the students’ perception of the implementation of MGlab Netlux Software in the Listening for Professional Context Class. This qualitative study used a personal interview method to collect the data. Nineteen English students at Listening for Professional context class in a private university in Yogyakarta were chosen as the subjects of this research. The results indicate that MGlab Netlux Software had already met the indicators of the class outline. The students also had positive responses toward the use of this Software. There were also several different perceptions on the weaknesses, difficulties in applying it. The researcher hopes that this research can be beneficial to readers, particularly English teachers who wish to seek out the students’ perceptions on the use of certain Software related to Computer Assisted Language Learning in teaching students.